Formulation a dual effect natural drag reduction agent - Siti Nuraffini , Kamarulizam (2012)
Transporting liquids in pipelines is considered as one of the most economically feasible methods due to the controlled and safe media these liquids are transported within. The transportation of liquids through strategic pipelines and for hundreds of kilometers is also considered as one of the most power consuming sectors due to the turbulent mode these liquids are transported with. Additional supporting pumping station along the pipeline was one of the solutions applied, but its application added an additional cost to the total cost of transportation. The addition of polymeric additives to the main flow was proven to be a successful solution to the pumping power dissipation in pipelines due to the visco-elastic properties of these polymers that can suppress the turbulent structures inside the pipe. Most of these polymeric additives are not biodegradable and not environmentally friendly. In this present work, a new environmental friendly, soluble and insoluble Drag Reducing Agents (DRA) is introduced. These new additives are driven from plant and byproduct of tin industries which are okra mucilage from lady finger and slag particles. The drag reduction performances of the new additives were tested in water and hydrocarbon media. The water-soluble okra mucilage and the slag powder drag reduction performance were tested in water solution. To test the okra mucilage in hydrocarbon solution, the solubility of the original okra mucilage was changed using grafting co-polymerization technique. The objective of this research is to investigate the effect of this novel DRA based on classical parameters which are additive concentration, fluid velocity, internal pipe diameter and pipe length. Experimental closed loop circulation rig consisted of three different pipes diameter (0.0381m D.I, 0.0254m D.I and 0.0127m D.I) with 2.0m pipe length were setup in order to accomplish the objectives. The transported solution was flowing through pipelines from tank into required testing section for pressure drop determination. A ball valve located at recirculation pipes used to control the flow rate of solution entering testing section the flow meter sensor and pressure sensors located at each testing section will give reading at screen by SCADA software. From experimental results, highest Percentage Drag Reduction (%Dr) were obtained on 0.0381m D.I with 78% flowing through Re equal to 29017.44, 1000ppm and 0.5m pipe length for hydrocarbon liquid and 80% flowing through Re equal to 118235.42, 1000ppm and 0.5m for water as transported media. For slag particles analysis, highest %Dr was obtained on 0.0381m D.I with 70% flowing through Re equal to 29017.44, 1000ppm and 0.5m pipe length. While, for water, highest %Dr where obtained at 0.0381m D.I with 80% flowing through Re = 118235.42, 1000ppm and 0.5m pipe length. The fluid velocity effect give increment and decrement pattern depend on Re-%Dr relation curve. Increasing additive concentration and pipe diameter will increased the %Dr. The %Dr reading for the pipe length effects gives unnoticeable changes. However, it is predicted to decrease for polymeric DRA since the breakup of polymer when facing shear stress. Time consumption shows polymer are able to resist increment of pressure drop at certain period. However, suspended solid DRA show consistent %Dr reading with time consumption. A mathematical expression by using STATISTICA software was developed to delineate and verified the real mechanism of Drag Reduction (DR). As a conclusion, new greener DRA were successfully introduced and its effectiveness in improving the flow was proven experimentally.